Job Stress, Burnout, Work-Life Balance, Well-Being, and Job Satisfaction Among Pathology Residents and Fellows. Issue 4 (21st February 2020) - Kelly, Melissa; Soles, Ryan; Garcia, Edna; Kundu, Iman
Abstract: Objectives: The study explored job stress, burnout, work-life balance, well-being, and job satisfaction among pathology residents and fellows. The aims were to examine the prevalence and sources of stress and burnout, as well as identify resources to promote work-life balance and well-being and prevent burnout. Methods: The study used a cross-sectional survey deployed online to a large national sample of pathology residents and fellows. Results: Job stress and burnout were prevalent, with more than a third of the respondents reporting that they were currently experiencing burnout. The respondents, particularly residents, were struggling with academics, and higher percentages were struggling with work-life balance and emotional well-being. Overall, the majority of respondents who rated their work-life balance indicated that it was poor or fair. Among the factors contributing to job stress and burnout and detracting from work-life balance, workload was the leading factor. Conclusions: The factors contributing to job stress and burnout included organizational factors such as workload, value, and aspects of the learning environment, as well as personal factors such as work-life integration. One of the overarching implications is the need to address a range of interdependent considerations in designing resources to reduce job stress, promote work-life balance, and prevent burnout.